WAIN: Wireless Ad Hoc in Infrastructure Network - Muthusamy, Yogeswari; Krishnan, Jaya Kumar (2008 International Symposium on Information Technology, 2008)
Wireless Local Area Network (WLAN) has grown into a large and diverse field of research, which span from power control to privacy and security. WLAN can be operated in two modes: infrastructure and ad hoc mode. Coverage and capacity limitation in infrastructure network causes performance and throughput to degrade. As a step to overcome this crucial problem, ad hoc mode is integrated in infrastructure network. Such architecture, recognized as WAIN (Wireless Ad Hoc in Infrastructure Network) in this paper. WAIN eliminates one hop capabilities of infrastructure network to multihop. Besides, it allows users to make use of ad hoc connections to forward data to avoid congestion at Access Point (AP) which in return improves overall network capacity. In this paper, I proposed time based routing algorithm to enhance the efficiency and network throughput.